Teachers’ perspectives and practices on biodiversity web portals as an opportunity to reconnect education with nature - Picanço, Ana; Arroz, Ana Moura; Amorim, Isabel R.; Matos, Sónia; Gabriel, Rosalina (Environmental Conservation, 2021)
Biodiversity loss is a complex issue and a risk that education cannot overlook. Teachers play a crucial role in how biodiversity, and in particular local biodiversity, is understood. To provide insight into how to improve communication on the subject, we investigate teachers’ perspectives and social representations regarding biodiversity, their fluency in terms of Internet use, their familiarity with biodiversity web portals and perceived pedagogical usefulness of technology. A sample of 243 K–12 schoolteachers of multiple scientific domains from eight Azorean islands answered an online survey, including three free-word association tests using inductive terms such as ‘Internet’, ‘biodiversity’ and ‘familiar biodiversity portals’. Overall, the schoolteachers failed to incorporate the multidimensionality of the biodiversity concept (including natural science teachers) or to show technological fluency, and they tended not to use biodiversity web portals as tools to engage students in teaching activities. Our results indicate that teachers’ perspectives about biodiversity need to be broadened and improved and that it is worth exploring whether information and communication technology represents a window of opportunity to do so. As an example, biodiversity web portals, which are widely recognized as trustworthy information repositories, may be used to engage teachers in this endeavour.
Publisher: Cambridge University Press
Keywords: Azores; ICT; biodiversity education; digital education; free-word association; nature experience; place-based education; social representations